Idade de desmame: respostas comportamentais, fisiológicas e zootécnicas de cordeiros mestiços Santa Inês Dorper e ovelhas Santa Inês - Rodrigues, Alice Deléo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The sheep breeding stands out as an opportunity in Brazilian livestock. For this reason, there is growing demand for information about the species, including information of management strategies to improve the productive system. In this context, 44 Santa Inês ewes and 58 ½ Santa Inês ½ Dorper lambs were evaluated during two consecutive lactations in order to determine the effects of two weaning ages, at 45 or at 60 days of age. In this study, behavioral measurements and blood samples were taken at weaning and also after it to determine the cortisol levels through administration of adrenocorticotropic hormone (ACTH). Cortisol levels, behavior measurements, weight and weight gain were analyzed using proc Mixed of SAS program. Means tests were done with 5% of significance (P<0.05). Cortisol levels at weaning for ewes and lambs were not different for the two weaning ages evaluated. For ewes, the highest cortisol levels were observed 24 h after weaning and the establishment of basal levels occurred 48 h after weaning. For lambs, on the other hand, reductions in cortisol levels were verified 6 and 12 h after weaning and establishment of basal levels one day after. After ACTH administration, cortisol curves aspect for ewes and lambs were very similar, therefore, highest liberation of cortisol was verified for the ewes. Between the five ewes with highest cortisol levels, 57.14% of their lambs had cortisol higher than the other cortisol lambs means. For weaning and ACTH administration, the response profile of ewes was repeated over the two years of evaluation (P<0.0001). For lambs, also no differences were found for weight and weight gain in the two ages of weaning, at 45 and at 60 days (P=0.11). Positive correlations between weight and high cortisol levels and between weight gain and lower cortisol levels were also verified. Lamb´s behaviors “Feeding, Inactivity and Standing in the shadow were influenced by weaning age and the ...

A ovinocultura vem ganhando destaque na agropecuária brasileira. Neste contexto, o estabelecimento de idade adequada para o desmame é fundamental para melhorar a produtividade. Por este motivo, é crescente a demanda por informações básicas sobre a espécie, incluindo estratégias de manejo que aperfeiçoem o sistema produtivo. Deste modo, 44 ovelhas Santa Inês e 58 cordeiros mestiços ½ Santa Inês ½ Dorper foram avaliados durante duas lactações com o objetivo de se conhecerem os efeitos de duas idades de desmame, aos 45 e aos 60 dias de idade. Neste estudo, foram feitas análises comportamentais e colheitas de sangue ao desmame e também colheitas para determinação dos níveis de cortisol dos animais após a administração de hormônio adrenocorticotrófico (ACTH). Os dados de cortisol, comportamento, peso e ganho de peso foram analisados pelo proc Mixed do SAS. Os testes de médias foram feitos com nível de significância de 5% (P<0,05). Os níveis de cortisol ao desmame das ovelhas e dos cordeiros não foram diferentes para as duas idades de desmame avaliadas. Para as ovelhas, os maiores valores foram observados 24 h após o desmame e restabelecimento dos níveis basais 48 h após o desmame. Para os cordeiros, entretanto, verificou-se redução nos níveis de cortisol 6 e 12 h após o desmame e restabelecimento dos níveis basais um dia depois. Após a administração de ACTH, o perfil da curva de cortisol dos cordeiros e das ovelhas foi bastante semelhante, embora maior liberação de cortisol tenha sido verificada para as ovelhas. Entre as cinco ovelhas com maior concentração de cortisol, 57,14% dos seus cordeiros apresentaram liberação de cortisol superior à média dos demais cordeiros. Para as ovelhas, tanto no desmame quanto na administração de ACTH, o perfil de resposta se repetiu ao longo dos dois anos de avaliação (P< 0,0001). Para os cordeiros também não foram verificadas diferenças no peso e no ganho de ...
Keywords: Ovino - Criação; Produção animal; Ovino - Fisiologia; Ovino - Comportamento; Hidrocortisona; Sheep